Segmentation and Cell Counting of Fluorescence Oral Cancer Cell Images Using Morphological Operations - Azman, Muhammad Amirul (Universiti Teknologi PETRONAS, 2016)
By definition, image processing is a method in order to enhanced or extract some information from the operations. Image processing involved three basic steps which are importing an image through image acquisition tools, image analysis and manipulation and image output based on image analysis. Image processing involved in almost every kind of application such as in medical field, remote sensing, video processing and etc. Segmentation are one of the technique in image processing which remove unnecessary background from the image and extract only useful information in an image. Segmentation is a primary step in cell counting and quantification of cells in medical diagnosis and treatment.